2012
DOI: 10.1262/jrd.11-108n
|View full text |Cite
|
Sign up to set email alerts
|

Purification of N-acetyllactosamine-binding Activity from the Porcine Sperm Membrane: Possible Involvement of an ADAM Complex in the Carbohydrate-binding Activity of Sperm

Abstract: Abstract. Although the importance of carbohydrate recognition by sperm during egg zona pellucida binding has been widely reported, the sperm molecular species that recognize the carbohydrates are poorly characterized. Our previous cytochemical study indicated that two kinds of carbohydrate-binding proteins are expressed on porcine sperm heads-one recognizes N-acetyllactosamine (Galβ1-4GlcNAc-), and the other recognizes the Lewis X structure (Galβ1-4(Fucα1-3) GlcNAc-). For this report, we used proteomic techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…There are few reports of glycan affinity of ADAMs proteins. Authors of one previous publication using asialo-α1-acid and asialo-aga-lacto- α1-acid affinity chromatography, reported that N -acetyllactosamine but not Le X had affinity for ADAM5 from epididymal boar spermatozoa (Mori et al ., 2012). On the contrary, we found that porcine epididymal and ejaculated spermatozoa recognize N -acetyllactosamine but bind much less N -acetyllactosamine than suLe X (Silva et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of glycan affinity of ADAMs proteins. Authors of one previous publication using asialo-α1-acid and asialo-aga-lacto- α1-acid affinity chromatography, reported that N -acetyllactosamine but not Le X had affinity for ADAM5 from epididymal boar spermatozoa (Mori et al ., 2012). On the contrary, we found that porcine epididymal and ejaculated spermatozoa recognize N -acetyllactosamine but bind much less N -acetyllactosamine than suLe X (Silva et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%